KARAKTERISTIK TAFSIR FI ZHILAL AL-QUR'AN - Zaidi, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2021)
Abstract Tafsir fi Zhilal Quran was written in the range of 1952 to 1965. He had time to revise the first thirteen juz of his interpretation during his long detention1. This interpretation led Sayid Qutub to explore the various moral messages of Islam that were conveyed through Muhammad's treatises, which strengthened faith and could provide a perfect ideological foundation. It was so phenomenal that Sayid Qutub wrote a fi dzilal al-quran interpretation, with its unique methods and characteristics, rich in literary and social language in his dakwa, inviting and inviting in a beautiful language style.Sayid qutub can complete his Tafsir in prison with enthusiasm and enthusiasm in writing his tafsir, with the aspiration to provide the best legacy for future generation.